Intraoperative bleeding model for swine gastric endoscopic submucosal dissection via heparinization - Masunaga, Teppei; Sasaki, Motoki; Sato, Moe; Minezaki, Daisuke; Morioka, Kohei; Tojo, Anna; Sakurai, Hinako; Iwata, Kentaro; Miyazaki, Kurato; Kubosawa, Yoko; Mizutani, Mari; Akimoto, Teppei; Takatori, Yusaku; Kawasaki, Shintaro; Matsuura, Noriko; Nakayama, Atsushi; Sujino, Tomohisa; Takabayashi, Kaoru; Yahagi, Naohisa; Nakajima, Kiyokazu; Kato, Motohiko (Endoscopy International Open, 2024)
Background and study aims: Live swine have a high degree of coagulation and aggregation and using them for training about how to manage intraoperative bleeding during endoscopic submucosal dissection (ESD) is unsatisfactory. This study aimed to identify the appropriate heparin dose in an intraoperative bleeding model and validate its applicability.Methods: First, we explored the dose of heparin required for a swine bleeding model in which the activated clotting time reached and maintained the upper limit of measurement (1500 s) after 10 minutes. Second, we compared intraoperative bleeding and hematoma frequency during ESD for 2-cm lesions between the heparinized bleeding model and control groups. Intraoperative bleeding was classified according to the Forrest classification.Results: The combination of a bolus (300 U/kg), continuous infusion (300 U/kg/h), and a bolus dose (150 U/kg) of heparin 10 minutes after the first infusion was identified as the dose for the bleeding model. Five ESDs were performed in each heparinized bleeding model and the control group. The median number of intraoperative bleeds was significantly higher in the heparinized model than in the control group (5 interquartile range [IQR] 4–7 vs. 3 [IQR 0–4, P = 0.028). All of the intraoperative bleeding events oozing (Forrest Ib) rather than spurting (Forrest Ia). The median number of hematomas was significantly higher in the heparinized model group than in the control group (3 [IQR 1–4] vs. 0 [IQR 0–1], P = 0.023).Conclusions: High doses of heparin significantly increased intraoperative bleeding and hematoma during swine ESD.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Quality and logistical aspects; Training